Religious Cultural Strategy in Forming Character of Akhlakul Karimah in Students - Misriyani, Dwi; Alhamid, Idrus; Iribaram, Suparto (Al-Mudarris, 2025)
Religious culture as a strategy is an important step in shaping the character of students towards a more religious "Akhlakul Karimah". Religious culture as a strategy is often the subject of discourse, especially those that discuss the development, utilization, and implications so that the discourse on the implementation of religious culture as a school strategy in shaping religious character "Akhlakul Karimah" tends to be neglected in scientific discussions. In line with that, this study focuses on the question "How is the implementation of religious culture as a school strategy in shaping the religious character of "Akhlakul Karimah" in students?" To answer this question, this study uses a qualitative approach by conducting observations and interviews with teachers and students. The findings in this study show that religious culture is not only an effective and sustainable strategy in shaping "akhlakul karimah" religious character in learners but also equips learners with relevant values and skills for the future. Religious culture as a strategy is implemented by schools through the implementation of a multicultural curriculum and interfaith activities among learners that prioritize the development of "Akhlakul Karimah" religious values